2019
DOI: 10.1111/gcbb.12622
|View full text |Cite
|
Sign up to set email alerts
|

A spatiotemporal assessment of field residues of rice, maize, and wheat at provincial and county levels in China

Abstract: China has a huge resource potential for biomass‐based renewable energy development, but the resources of field residues are still not effectively used. Rice, maize, and wheat made up 89% of staple crop production in China in 2009. A comprehensive assessment of field residues of these three crops is necessary for the development of biomass‐based industries. This research was based on multiyear county‐level data of crop production, area and yield, as well as the crop phenology information from agrometeorological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The CRCA mapping is important for monitoring conservation tillage and agricultural subsidy policy application. Many studies have revealed the potential of crop residue covered area mapping using medium spatial resolution remote sensing images [58][59][60][61]. Considering the inhomogeneity and randomness resulting from human management difference, the Chinese high spatial resolution GF-1 B/D image and developed MSCU-net+C deep learning method is used to mapping CRCA in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The CRCA mapping is important for monitoring conservation tillage and agricultural subsidy policy application. Many studies have revealed the potential of crop residue covered area mapping using medium spatial resolution remote sensing images [58][59][60][61]. Considering the inhomogeneity and randomness resulting from human management difference, the Chinese high spatial resolution GF-1 B/D image and developed MSCU-net+C deep learning method is used to mapping CRCA in this study.…”
Section: Discussionmentioning
confidence: 99%
“…At country level, other studies have also assessed the environmental potential of biomass residues. 22,27,28 Of all these studies, a more limited number 19,21,29,30 have used a bottom-up approach to model the environmental constraints spatially to estimate the biomass residue removal rate at field level. All of these studies contributed, to differing extents, to an understanding of how the spatial heterogeneity in agroecological conditions affect the environmental potential of biomass residues for bioenergy.…”
Section: Introductionmentioning
confidence: 99%
“…China has a huge potential of agricultural residue resources to offer, but the residues are not effectively used, especially in terms of bioenergy production [1]. Apart from using residues as livestock feed, rural household fuel, paper pulp, and substrate for mushroom cultivation, agricultural residue-based bioenergy production is now a popular practice in many countries, such as Denmark, Sweden, the UK, Spain, and China [2].…”
mentioning
confidence: 99%
“…Therefore, it is necessary to answer the questions arising about the extent of the potential of available agricultural residues and their spatial distribution. In recent decades, an increasing number of studies estimating the potential of biomass feedstocks were carried out at global, national, or regional scales by using different research methods, i.e., either statistical [2,[7][8][9][10][11][12][13][14][15] or geographic information system (GIS)-based methods [1,6,[16][17][18][19][20]. However, evaluated quantities of biomass residues available for bioenergy production vary greatly among different studies due to differences in the types of crop residues analysed, residue to product ratios, and constraining factors taken into account.…”
mentioning
confidence: 99%